Sarthaks Test
0 votes
139 views
in Mathematics by (15.0k points)

Add: 

p (p − q), q (q − r) and r (r − p)

1 Answer

0 votes
by (24.8k points)
selected by
 
Best answer

First expression = p (p − q) = p2 − pq

Second expression = q (q − r) = q2 − qr

Third expression = r (r − p) = r2 − pr

Adding the three expressions, we obtain

Therefore, the sum of the given expressions is p2 + q2 + r2 − pq − qr − rp.

Welcome to Sarthaks eConnect: A unique platform where students can interact with teachers/experts/students to get solutions to their queries. Students (upto class 10+2) preparing for All Government Exams, CBSE Board Exam, ICSE Board Exam, State Board Exam, JEE (Mains+Advance) and NEET can ask questions from any subject and get quick answers by subject teachers/ experts/mentors/students.

Categories

...